Genomic variation in microbial populations inhabiting the marine subseafloor at deep-sea hydrothermal vents. Issue 1 (December 2017) - Anderson, Rika; Reveillaud, Julie; Reddington, Emily; Delmont, Tom; Eren, A. Murat; McDermott, Jill; Seewald, Jeff; Huber, Julie
Abstract Little is known about evolutionary drivers of microbial populations in the warm subseafloor of deep-sea hydrothermal vents. Here we reconstruct 73 metagenome-assembled genomes (MAGs) from two geochemically distinct vent fields in the Mid-Cayman Rise to investigate patterns of genomic variation within subseafloor populations. Low-abundance populations with high intra-population diversity coexist alongside high-abundance populations with low genomic diversity, with taxonomic differences in patterns of genomic variation between the mafic Piccard and ultramafic Von Damm vent fields. Populations from Piccard are significantly enriched in nonsynonymous mutations, suggesting stronger purifying selection in Von Damm relative to Piccard. Comparison of nineSulfurovum MAGs reveals two high-coverage, low-diversity MAGs from Piccard enriched in unique genes related to the cellular membrane, suggesting these populations were subject to distinct evolutionary pressures that may correlate with genes related to nutrient uptake, biofilm formation, or viral invasion. These results are consistent with distinct evolutionary histories between geochemically different vent fields, with implications for understanding evolutionary processes in subseafloor microbial populations. The warm subseafloor at deep-sea hydrothermal vents hosts diverse microbial communities. Here, Anderson et al. reconstruct 73 metagenome-assembled genomes from two geochemically distinct hydrothermal vent fields, showing different patterns of genomic variation among diverse microbial taxa.